The complete mitochondrial genome of the Cyathochromis obliquidens. Issue 1 (1st January 2017) - Wen, Xiangru; Wang, Cailin; Li, Man; Wang, Haiyan; Qi, Dashi
Abstract: The Cyathochromis obliquidens, the only member of Cyathochromis genus, is widely spread in Africa. In this study, we firstly reported the complete mitochondrial genome of C. obliquidens . The whole mitochondrial genome is 16, 581 bp in length, including 2 ribosomal RNA genes, 22 transfer RNA genes and 13 protein-coding genes. Its GC content is 45.94%, similar to the other species from the same family, like Alticorpus geoffreyi (45.82%). We also analyzed the complete mitochondrial genome of C. obliquidens and its phylogenic relationship with other 14 related species, which would help our better understanding of the evolution of Cichlidae mitochondrial genome.